2011
DOI: 10.1016/j.pain.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-selective phenotypic switch in primary afferent neurons contributes to neuropathic pain

Abstract: Pain is normally mediated by nociceptive Aδ and C fibers, while Aβ fibers signal touch. However, after nerve injury, Aβ fibers may signal pain. Using a genetic model, we tested the hypothesis that phenotypic switching in neurotransmitters expressed by Aβ afferents might account for heritable differences in neuropathic pain behavior. The study examined selection-line rats in which one line, high autotomy (HA), shows higher levels of spontaneous pain in the neuroma neuropathy model, and of tactile allodynia in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 76 publications
2
45
0
Order By: Relevance
“…78 Studies performed with genetically similar rats that expressed either a high (HA) or low (LA) propensity to develop allodynia after peripheral nerve injury showed that the HA rats showed a 10-fold increase in CGRP in large-diameter DRG neurons. 143,144 The increase in CGRP in these neurons corresponded to the development of behavioral signs of tactile allodynia and central sensitization in the HA rats. 143,144 The intrathecal administration of the CGRP receptor antagonist BIBN4096BS (olcegepant) blocked behavioral and neurochemical signs of central sensitization without altering baseline nociceptive thresholds.…”
Section: Calcitonin Gene–related Peptide and Pain Modelsmentioning
confidence: 90%
“…78 Studies performed with genetically similar rats that expressed either a high (HA) or low (LA) propensity to develop allodynia after peripheral nerve injury showed that the HA rats showed a 10-fold increase in CGRP in large-diameter DRG neurons. 143,144 The increase in CGRP in these neurons corresponded to the development of behavioral signs of tactile allodynia and central sensitization in the HA rats. 143,144 The intrathecal administration of the CGRP receptor antagonist BIBN4096BS (olcegepant) blocked behavioral and neurochemical signs of central sensitization without altering baseline nociceptive thresholds.…”
Section: Calcitonin Gene–related Peptide and Pain Modelsmentioning
confidence: 90%
“…These changes may include, but are not limited to, dysregulation of genes (Dobremez et al, 2005), suppressing inhibitory and/or enhancing facilitatory descending modulations (Suzuki et al, 2004; Rahman et al, 2008), attenuated glutamate uptake (Binns et al, 2005), and increased pain-inducing peptides in DDH neurons (Nitzan-Luques et al, 2011). However, to the best of our knowledge, it is not yet known if peripheral nerve injury alters excitatory and/or inhibitory miniature synaptic transmission in deep dorsal horn, which can play a critical role in mediating neuropathic allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Those cells secrete substances involved in the process of degeneration and regeneration and they also can increase sensitivity of nerve endings. Following a peripheral nerve injury, pathological changes can also occur within CNS (Nitzan-Luques et al, 2011) and metabolism of spinal cord neurons changes. Some changes in CNS appear to be associated with enhanced neurotransmission via the NMDA, AMPA and NK-1 receptors (Pickering et al, 2011;Zhuo, 2007).…”
Section: Introductionmentioning
confidence: 99%